Fine-scale movement response of juvenile brown trout to hydropeaking - Naudascher, Robert; Boes, Robert M.; Fernandez, Vicente; Wittmann, Joël; Holzner, Markus; Vanzo, Davide; Silva, Luiz G.M.; Stocker, Roman (The Science of the total environment, 2024)
Juvenile fish are known to be the most impacted during hydropeaking events due to stranding or uncontrolled drift resulting from changes to water depth and flow velocity. To shed light on their response to such hydraulic alterations, we coupled flume experiments with image-based fish tracking and quantified the fine-scale movement behavior of wild (n = 30) and hatchery-reared (n = 38) brown trout (Salmo trutta) parr. We exposed fish to two distinct hydropeaking treatments in a laterally inclined (14 %) flume section stocked with real cobbles to create refuge and heterogeneous hydraulic conditions. Fish were individually acclimated (20 min) to baseflow (Q = 1.6 L s-1) and then exposed to three consecutive hydropeaking events, reaching peakflows tenfold larger than baseflow (Q = 16 L s-1). We found that, within just minutes, fish exhibited fine-scale movement responses to cope with the change of hydrodynamic conditions. Fish moved perpendicular to the main flow direction to shallow areas as these became submerged during discharge increase, holding position at low velocity zones. This resulted in a significant difference (p < 0.001) in lateral occupancy of the experimental section between baseflow and peakflow. During peakflow, fish occupied specific positions around cobbles and exhibited swimming behaviors, including bow-riding and entraining, that allowed them to hold position while likely minimizing energy expenditure. As a result, swimming distance reduced 60–70 % compared to baseflow. During the decrease in discharge following peakflow, fish abandoned areas falling dry by moving laterally. In the treatment with the larger down-ramping rate, the time to initiate relocation was lower while the relocation speed was higher. This study shows that, for the conditions investigated here, brown trout parr is capable of swiftly deploying multiple behavioral responses to navigate rapid changes in hydrodynamic conditions. These findings can be incorporated into habitat modeling and improve our capacity to inform hydropeaking mitigation efforts. [Display omitted] •Trout parr respond to hydropeaking within mere minutes.•To cope with high flows, they swiftly relocate laterally and reduce exploratory behavior.•Increased down-ramping rates result in shorter response times and increased relocation speed.